Forecasting the Impact of Increasing Regency/City Minimum Wage on the Total Open Unemployment Rate in Sidoarjo Regency for 2024-2030 - Pramesari, Alifia Hayunda; Setiyono, Wisnu Panggah; Fitriyah, Hadiah (International Journal of Economics Development Research (IJEDR), 2024)
The increase in the minimum wage for Sidoarjo Regency from 2013 to 2023 shows a sharp increase. This makes open unemployment even higher and places Sidoarjo Regency in first place with the highest number of unemployed in East Java. If the minimum wage in Sidoarjo Regency experiences a very significant increase in the following years, more companies will go bankrupt or even move outside Sidoarjo Regency to prevent greater losses, resulting in more unemployment in Sidoarjo Regency. This research aims to determine the impact of forecasting increases in the minimum wage on open unemployment in Sidoarjo Regency every year 2024 to 2030. This research uses the ARIMA (0,1,0) model, which is then analyzed using IBM SPSS Statistics 25 version. The research results show that open unemployment in Sidoarjo Regency over the next 6 (six) years is likely to increase by 0.43% every year. This happens because of the increase in the minimum wage which tends to get higher every year.